2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--35343
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Connecting Funds of Knowledge to Beliefs about Performance, Classroom Belonging, and Graduation Certainty for First-generation College Students

Abstract: with an MS in Industrial Engineering and PhD in Engineering Education. Dina is a 2016 recipient of the National Science Foundation's Graduate Research Fellowship and an Honorable Mention for the Ford Foundation Fellowship Program. Her research interest focuses on changing the deficit base perspective of first-generation college students by providing asset-based approaches to understanding this population. Dina is interested in understanding how first-generation college students author their identities as engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
(36 reference statements)
2
10
0
Order By: Relevance
“…Specifically, students' home tinkering knowledge supported their interest in engineering and perception of their abilities to perform well and understand engineering course material. This finding builds on our previous research, which demonstrated that this fund of knowledge directly supported first-generation college students' certainty of graduating (Verdin et al, 2020). Our previous study also found that tinkering knowledge supported their beliefs about doing well in engineering coursework, which in turn helped their certainty of majoring in engineering (Verdin et al, 2020).…”
Section: Tinkering Knowledge From Homesupporting
confidence: 86%
See 1 more Smart Citation
“…Specifically, students' home tinkering knowledge supported their interest in engineering and perception of their abilities to perform well and understand engineering course material. This finding builds on our previous research, which demonstrated that this fund of knowledge directly supported first-generation college students' certainty of graduating (Verdin et al, 2020). Our previous study also found that tinkering knowledge supported their beliefs about doing well in engineering coursework, which in turn helped their certainty of majoring in engineering (Verdin et al, 2020).…”
Section: Tinkering Knowledge From Homesupporting
confidence: 86%
“…Becoming a certain kind of person (e.g., by forming an engineering role identity) is critical in helping college students to sustain motivation and engagement in the process of learning (National Academies of Science, Engineering, and Medicine, 2018). Ample studies have documented how an engineering identity supports students' intentions to choose a major in engineering (Godwin & Kirn, 2020), supports persistence beliefs (Jones et al, 2013; Patrick et al, 2018; Verdín, 2021a, 2021b), bolsters confidence in their choice of major (Verdín & Godwin, 2021; Verdín, Godwin, Sonnert, & Sadler, 2018), and helps them pursue an engineering industry‐related career (Verdín & Godwin, 2017). More recently, Verdín (2024) found that Latinx students' engineering role identity positively impacted their perceptions of their future career outcomes, which encompassed beliefs about obtaining their desired engineering job and succeeding in their chosen career.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Museus et al (2017) documented that students' sense of belonging was supported through four culturally engaging elements, (1) when students felt that "their cultural knowledge, backgrounds, and identities were valued"; (2) students' ability to connect with faculty members, staff, or peers with similar backgrounds and experiences; (3) when institutional agents made information about opportunities and support resources more visible to students; and (4) establishing trust with one faculty or staff member (p. 192). Scholars have drawn awareness to the disconnect between engineering courses and students' ability to connect and leverage their household and cultural knowledge systems to their learning (Smith & Lucena, 2016;Verdín, Smith, & Lucena, 2019;Verdín et al, 2020). Thus, finding ways to incorporate students' household and cultural knowledge systems into engineering may provide an opportunity for minoritized women to develop a sense of belonging.…”
Section: Discussionmentioning
confidence: 99%
“…Bandura (1997) argues that self-efficacy beliefs at an early age are task-specific and as individuals mature, overtime, self-efficacy beliefs become more generalized in a given domain. The relationship between students' self-efficacy beliefs and academic persistence has had mixed results, with some studies demonstrating significant relationships (e.g., Bettencourt et al, 2020;Brown et al, 2008;Hackett et al, 1992;Lent et al, 1986;Multon et al, 1991;Verdín et al, 2020) and other studies demonstrating no significant relationships, direct or indirect (e.g., Lee et al, 2015;Patrick et al, 2018). Interestingly, in the present study, beliefs about one's ability to understand engineering content material and its relationship with persistence beliefs were contingent on group membership.…”
Section: Certainty Of Graduating With An Engineering Degreementioning
confidence: 99%
“…Share student examples and stories or document approaches that include a component of their culture, community, or family life in the projects they have created; this will be especially important for personal projects created in the space. Ensuring that making activities promote a sociocultural approach can ensure that individuals' funds of knowledge are elevated [46] and that their sense of belonging is improved [10,12,13].…”
Section: Recommendations For Engineering Education Making Space Leadersmentioning
confidence: 99%